A local approach to cleavage fracture modeling: An overview of progress and challenges for engineering applications. (January 2018) - Ruggieri, Claudio; Dodds, Robert H.
Highlights: Overview of recent progress in local approach to cleavage fracture (LAF) and the Weibull stress concept. Incorporation of plastic strain effects in terms of eligible Griffith-like microcracks which effectively control cleavage. Recent results to predict specimen geometry effects on cleavage fracture toughness values for pressure vessel steels. Critical discussion of key issues and challenges related to engineering applications of the Weibull stress approach. Abstract: This paper provides an overview of recent progress in probabilistic modeling of cleavage fracture phrased in terms of a local approach to fracture (LAF) and the Weibull stress concept. Emphasis is placed on the incorporation of plastic strain effects into the probabilistic framework by approaching the strong influence of constraint variations on (macroscopic) cleavage fracture toughness in terms of the number of eligible Griffith-like microcracks which effectively control unstable crack propagation by cleavage. Some recent results based on a modified Weibull stress model to predict specimen geometry effects on J c -values for pressure vessel grade steels are summarized in connection with an engineering procedure to calibrate the Weibull stress parameters. These results are compared against corresponding fracture toughness predictions derived from application of the standard Beremin model. Finally, the robustness of LAF methodologies, including specifically the Weibull stress approach, is critically examined along with a discussion of key issues and challenges related to engineering applications in fracture assessments of structural components.